2014
DOI: 10.1021/ef5017686
|View full text |Cite
|
Sign up to set email alerts
|

Cu-Modified Manganese Ore as an Oxygen Carrier for Chemical Looping Combustion

Abstract: A new type of Mn-based oxygen carrier was prepared by impregnating manganese ore with copper nitrate solution. Cyclic reduction and oxidation reactivity of the materials was investigated in a fluidized-bed reactor. The potential use of these oxygen carriers for chemical looping combustion (CLC) was examined. The reactivity of the manganese ore can be highly improved by impregnation of copper. The reactivity of the oxygen carrier reduction is higher with a larger amount of copper impregnated. However, the degre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 42 publications
(23 citation statements)
references
References 26 publications
0
23
0
Order By: Relevance
“…The addition of Cu increased the oxygen transport capacity with high fuel conversion. The synergetic effects to improve oxygen transport capacity with high fuel conversion have been observed when copper is coated on manganese ore or Hematite [28][29]. In these studies, oxygen transport capacity with high selectivity was dramatically enhanced six times.…”
Section: Selectivity Of Ocs In Converting Syngas To Co 2 and H 2 Omentioning
confidence: 89%
“…The addition of Cu increased the oxygen transport capacity with high fuel conversion. The synergetic effects to improve oxygen transport capacity with high fuel conversion have been observed when copper is coated on manganese ore or Hematite [28][29]. In these studies, oxygen transport capacity with high selectivity was dramatically enhanced six times.…”
Section: Selectivity Of Ocs In Converting Syngas To Co 2 and H 2 Omentioning
confidence: 89%
“…When Cu is added to Mn ore a possible synergistic effect was noted and potential CLOU properties were observed. While all of the samples showed complete CO conversion, the major influence this addition had was a prolonged conversion time, likely due to an increased oxygen transport capacity (Xu et al, 2014). The addition of Cu to Fe ore also showed a higher CO conversion as well as an increase in C conversion .…”
Section: Mixed Ores and Modificationsmentioning
confidence: 94%
“…They found that the Cu-Mn mixed oxides was able to generate gaseous oxygen up to 700 ºC and have good reactivity with CH4 but CO was present in the outlet stream. Depending on the Cu-Mn mixed oxide phase formed during the oxygen carrier preparation: CuMn2O4 [7,20] or Cu1.5Mn1.5O4 [19,21], the oxygen release can occur by two different reactions: 2…”
Section: Introductionmentioning
confidence: 99%